2021
DOI: 10.3390/cells10102656
|View full text |Cite
|
Sign up to set email alerts
|

Oxysterol 7-α Hydroxylase (CYP7B1) Attenuates Metabolic-Associated Fatty Liver Disease in Mice at Thermoneutrality

Abstract: Ambient temperature is an important determinant of both the alternative bile acid synthesis pathway controlled by oxysterol 7-α hydroxylase (CYP7B1) and the progression of metabolic-associated fatty liver disease (MAFLD). Here, we investigated whether CYP7B1 is involved in the etiology of MAFLD under conditions of low and high energy expenditure. For this, Cyp7b1−/− and wild type (WT) mice were fed a choline-deficient high-fat diet and housed either at 30 °C (thermoneutrality) or at 22 °C (mild cold). To study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…Moreover, ANGPTL4 has been described to be critical for BAT TRL uptake ( Dijk et al, 2015 ), and Angptl4 transcript levels were increased in cold-housed Cyp7b1 −/− mice. Of note, as described by others and us before ( Kakiyama et al, 2020 ; Evangelakos et al, 2021 ), Cyp7b1 is tightly associated with insulin resistance and cold-exposed Cyp7b1 −/− mice seem to be insulin-resistant. This might be explained by the reduced thermogenic activity and subsequent lower energy expenditure observed in Cyp7b1 −/− mice, which ultimately results in the development of obesity.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Moreover, ANGPTL4 has been described to be critical for BAT TRL uptake ( Dijk et al, 2015 ), and Angptl4 transcript levels were increased in cold-housed Cyp7b1 −/− mice. Of note, as described by others and us before ( Kakiyama et al, 2020 ; Evangelakos et al, 2021 ), Cyp7b1 is tightly associated with insulin resistance and cold-exposed Cyp7b1 −/− mice seem to be insulin-resistant. This might be explained by the reduced thermogenic activity and subsequent lower energy expenditure observed in Cyp7b1 −/− mice, which ultimately results in the development of obesity.…”
Section: Discussionsupporting
confidence: 69%
“…In mice, loss of Cyp7b1 resulted in increased levels of oxysterols ( Li-Hawkins et al, 2000 ), which are precursors of BA. Furthermore, Cyp7b1 deficiency has been linked to the development of liver steatosis and inflammation ( Setchell et al, 1998 ; Dai et al, 2014 ; Kakiyama et al, 2020 ; Evangelakos et al, 2021 ). Interestingly, our group has recently shown that the activation of BAT by cold not only stimulates the cholesterol flux to the liver but also induces the expression of hepatic Cyp7b1 , resulting in higher BA production ( Worthmann et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…As already described, housing mice under TN conditions leads to suppression of systemic lipid metabolism, and the levels of triglyceride and free fatty acid were reported to increase with thermoneutrality ( Evangelakos et al., 2021 ; Labbe et al., 2016 ). Similar to a previous study ( Wang et al., 2021 ), in our study, the administration of palmitic acid-induced apoptosis in human umbilical vein endothelial cells (HUVECs), and co-administration of BoyP suppressed this apoptosis ( Figure 5 H).…”
Section: Resultsmentioning
confidence: 56%
“…In general, mice are housed at a temperature of around 20°C to 22°C, a condition at which cold-induced activation of BAT is considered to develop; 29°C to 34°C is recognized as a thermoneutral temperature (TN) for mice ( Vialard and Olivier, 2020 ). Studies found that mice maintained under TN conditions develop systemic glucose intolerance ( Clayton and McCurdy, 2018 ), suppression of systemic lipid metabolism ( Evangelakos et al., 2021 ), and BAT dysfunction ( Cui et al., 2016 ). In NC mice, TN promoted BAT whitening and increased body or BAT weight, and both these effects were ameliorated by BoyP ( Figures 1 F, 1G, and S1 J–S1L).…”
Section: Resultsmentioning
confidence: 99%
“…Comparing to thermoneutrality-housing [ 160 ], cold exposure stimulates bile acid synthesis through induction of CYP7A1 [ 161 ], CYP8B1, CYP7B1 and CYP27A1 [ 162 , 163 ]. This is accompanied by changes in the microbiota composition and functionality [ 162 ].…”
Section: Strategies To Modulate the Bile Acid Poolmentioning
confidence: 99%